Effects of Ellagic Acid Supplementation on Jejunal Morphology, Digestive Enzyme Activities, Antioxidant Capacity, and Microbiota in Mice - Xu, Qiuying; Shen, Mingkang; Han, Yuxin; Diao, Hui (Frontiers in Microbiology, 2021)
Ellagic acid (EA), a plant polyphenol mainly found in nuts and fruits, exhibits various biological effects. However, the effects of EA on intestinal health remain poorly understood. Hence, the present study aimed to assess the effects of EA supplementation on jejunal morphology, digestive enzyme activities, antioxidant capacity, and microbiota in C57BL/6J mice. A total of 144 mice were randomly assigned to three treatments groups: the control (CON) group received a standard pellet diet, the 0.1% EA group received a standard pellet diet plus 0.1% EA, and the 0.3% EA group received a standard pellet diet plus 0.3% EA. The mice were killed at the end of the experimental period, and jejunal samples were collected. The results revealed that the mice in the 0.3% EA group had higher (P < 0.05) average daily gain and greater (P < 0.05) jejunal villus height than those in the CON group. In addition, the jejunal lactase and sucrase activities were higher (P < 0.05) in the 0.1% EA and 0.3% EA groups, and the alkaline phosphatase activity was higher (P < 0.05) in the 0.3% EA group than in the CON group. Compared with the CON group, the administration of EA increased (P < 0.05) the superoxide dismutase and catalase activities but decreased (P < 0.05) the malonaldehyde content in the jejunum. Moreover, the jejunal messenger RNA expression levels of nuclear factor-E2-related factor 2 (Nrf2) and haem oxygenase-1 (HO-1) were higher (P < 0.05) in the 0.3% EA group than in the CON group. Furthermore, compared with the CON group, the count of Escherichia coli decreased (P < 0.05), and that of Lactobacillus species increased (P < 0.05) in the 0.3% EA group. In general, our findings indicate that the administration of EA can enhance the growth of mice, promote intestinal development, increase the antioxidant capacity, and regulate the intestinal microbiota.